Prognosis for Cutaneous Melanoma by Clinical and Pathological Profile: A Population-Based Study - Buja, Alessandra; Bardin, Andrea; Damiani, Giovanni; Zorzi, Manuel; De Toni, Chiara; Fusinato, Riccardo; Spina, Romina; Vecchiato, Antonella; Del Fiore, Paolo; Mocellin, Simone; Baldo, Vincenzo; Rugge, Massimo; et al. (Frontiers in Oncology, 2021)
The incidence of cutaneous malignant melanoma (CMM) has been increasing steadily among white people for several decades. Meanwhile, there has also been a significant improvement in 5-year survival among patients with melanoma. The present study investigates the five-year melanoma-specific survival (MSS) for all cases of CMM recorded in 2015 by the Veneto Tumor Registry, taking both demographic and clinical variables and histopathologic features into consideration. This is a population-based cohort study. The cumulative melanoma-specific survival probabilities were calculated with the Kaplan-Meier method using different sociodemographic and clinical and histopathologic features. Cox’s proportional hazards model was ﬁtted to the data to assess the association between independent variables and MSS, calculating the hazard ratios (HR) relative to a reference condition, adjusting for sex, age, stage at diagnosis, mitoses, tumor infiltrating lymphocytes (TIL), growth phase (horizontal vs vertical), and morphology. The risk of death was 44% higher among males; each additional year of age was associated with an 8% higher risk of dying within 5 years (HR=1.03, 95% CI: 1.06-1.10, p=<0.001). Compared with patients with a melanoma in stage I, the risk of death was increased by 77% for stage II (HR 1.77, 95% CI: 0.97-3.25, p=0.04), almost four times higher for stage III (HR 3.85, 95% CI: 2.13-6.96, p<0.001), and thirty times higher for stage IV (HR 31.75, 95% CI: 12.57-80.20, p<0.001). Among the other variables included the model, only the presence of mitoses emerged as an independent risk factor for death. Kaplan-Meier MSS curves by TNM stage, presence of ulceration, number of mitoses, TILs, growth phase, and morphology at diagnosis are displayed. Confirming previous findings, male sex, older age and the presence of mitoses were independently associated with a higher risk of death at the multivariate analysis; histology only influenced survival among cases of lentigo maligna and acral melanoma, which had better prognoses than nodular melanoma. Neither growth phase, nor TIL were independently associated with survival. Data on survival by clinical and morphological characteristics could be useful in modelling, planning and managing the most appropriate treatment and follow-up plans for patients with CMM.